Local Development and Social Capital: The Case of Sotkamo - Esko Lehto; Jukka Oksa (European Regional Science Association (ERSA), 2003)
The paper discusses the role of social capital in the dramatic structural change that has taken place in the rural municipality of Sotkamo in north-eastern Finland. The main approach of this study is to observe the formation and use of social capital in important local events. Earlier definitions of local development have been based on factors such as natural resources, labour force, machines and tools, technology, knowledge and skills. The explanation based on social capital focuses on factors which increase and improve co-operation. Important issues of social capital are the existing rules of behaviour, the networks mediating these rules, and the trust amongst members of society that these rules are respected. In the case of Sotkamo the change has been the rise of tourism. Simultaneously this has meant the rise of Vuokatti as the central place in regional and local development. The paper is based on a questionnaire study and key-person interviews in Sotkamo. The paper discusses the following themes: What kind of actors and networks are participating in local development? Which actors are regarded as trustworthy in local development? What kinds of changes have occurred in the local identity and image? What kinds of struggles and coalitions of local power can be recognised? Results are analysed in the framework of social capital and local development. The study concludes that 'balanced' local development may take place, if the locality has the capacity of building networks that can meet the challenges of the future. Such networks should unite actors using both traditional local resources and new resources from outside of the locality. An important challenge is to balance the demands of economic restructuring and those of local community cohesion. This paper is based on the Finnish national study RESTRIM (Restructuring in Marginal Rural Areas: the role of social capital in rural development), a project that is funded by the European Union (for more, see http://www.abdn.ac.uk/arkleton/RESTRIM/).
Keywords: 330